1996
DOI: 10.1088/0031-8949/54/6/013
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar electron distributions in a non-uniform plasma embedded in a high-frequency electromagnetic field

Abstract: New self-similar distributions functions (EDF's) in a non-uniform plasma embedded in a non-uniform high frequency electromagnetic field are reported. The dependences of the EDF's on the degree of density nonuniformity, on the rate of electron heating due to inverse bremsstrahlung absorption of high frequency field, and on the value of the electric current in a plasma are established. It is shown how the EDF modi6cations i d uence the energy absorption of the electromagnetic field and the electron heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 18 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…For V E greater than V T (t) by a factor larger than 4 the same initial EDF first becomes elongated in the perpendicular direction to that of the laser polarization, and afterwards evolves as in the case V E /V T (t) > 2÷4. In both cases, far from the critical transition values of V E /V T (t), the field modified EDF may profitably be approximated by an EDF with a maxwellian shape and two different temperatures, perpendicular and parallel to the laser electric field (anisotropic bi-maxwellian EDF) [15][16][17][18]. 4).…”
Section: Account Of the Plasma Influencementioning
confidence: 99%
“…For V E greater than V T (t) by a factor larger than 4 the same initial EDF first becomes elongated in the perpendicular direction to that of the laser polarization, and afterwards evolves as in the case V E /V T (t) > 2÷4. In both cases, far from the critical transition values of V E /V T (t), the field modified EDF may profitably be approximated by an EDF with a maxwellian shape and two different temperatures, perpendicular and parallel to the laser electric field (anisotropic bi-maxwellian EDF) [15][16][17][18]. 4).…”
Section: Account Of the Plasma Influencementioning
confidence: 99%
“…With the expressions for the collision integrals (5) and (7), equation (4) is a nonlinear integro-differential equation for the EDF in the presence of a laser field. A huge number of papers (see, for instance, [3,4,[6][7][8][9][10][11][12][13][14][15][27][28][29][30][31][32]) have been devoted to the solution of this equation. Nevertheless, a general solution to this equation has still not been found.…”
Section: Basic Kinetic Equationmentioning
confidence: 99%
“…In [3] it was shown that, as a result of electron heating due to inverse bremsstrahlung absorption made possible by electron-ion collisions, in the process of plasma-laser interaction a distribution function is established, exhibiting a far-reaching depletion of slow electrons. Afterwards, a lot of papers were published along the same lines addressing, among others things, the influence on the EDF of the electron-electron collisions and the plasma spatial nonuniformity (see, for instance, [5][6][7][8][9][10][11][12][13][14][15]). It has been shown that the establishment of a field-modified EDF, like that obtained in [3], is responsible for a series of important physical consequences of direct concern to plasma physics applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations